Political Competition and the Limits of Political Compromise - Alexandre B. Cunha; Emanuel Ornelas (Center for Economic Studies and ifo Institute (CESifo), 2014)
We consider an economy where competing political parties alternate in office. Due to rent-seeking motives, incumbents have an incentive to set public expenditures above the socially optimum level. Parties cannot commit to future policies, but they can forge a political compromise where each party curbs excessive spending when in office if it expects future governments to do the same. We find that if the government cannot manipulate state variables, more intense political competition fosters a compromise that yields better outcomes, potentially even the first best. By contrast, if the government can issue debt, vigorous political competition can render a compromise unsustainable and drive the economy to a low-welfare, high-debt, long-run trap. Our analysis thus suggests a legislative tradeoff between restricting political competition and constraining the ability of governments to issue debt.
Keywords: E61; E62; H30; H63; 330; political turnover; efficient policies; public debt